Bella’s Anxieties in the Twilight Saga: New Moon - Monica Rachmat; Theophilus J Riyanto (Institute of Research and Community Outreach - Petra Christian University, 2013)
This paper tries to deal with the causes of Bella’s anxieties and the ways Bella overcomes them in The Twilight Saga: New Moon. To analyze the causes, I use two theories of anxiety; they are reality and neurotic anxiety. The two causes of Bella’s anxieties are insecure environment and traumatic experience. Bella uses four defense mechanisms to overcome her anxieties. They are denial, sublimation, acting out, and fixation. Bella denies her reality anxiety by denying her loneliness in the insecure environment. Besides, she uses acting out in order to release her reality anxiety and convert it to pleasure and satisfaction. Then she sublimates her anxiety into something useful, through studying. She is also fixating her anxiety to overcome both her reality and neurotic anxiety.